Pharmacological Blocking of Adiponectin Receptors Induces Alzheimer’s Disease-like Neuropathology and Impairs Hippocampal Function - Hui-Hui Guo; Hai-Ning Ou; Jia-Sui Yu; Suk-Yu Yau; Hector Wing-Hong Tsang (Biomedicines)
Background/Objectives: Previous studies have shown that adiponectin deficiency or blocking adiponectin receptors (AdipoRs) in the brain can lead to an Alzheimer’s disease (AD)-like neuropathology. While AdipoRs are abundantly expressed in peripheral tissues, the effects of blocking these receptors in the peripheral tissues on the brain are unclear. This study investigates the impacts of blocking AdipoRs with a peripheral administration of ADP400, an antagonist peptide that targets AdipoRs on cognitive performance, hippocampal adult neurogenesis, and AD-like neuropathology in mice. Methods: Adult mice were intraperitoneally administered with ADP400 peptide that blocks peripheral AdipoRs continuously for 21 days, followed by a battery of behavioral test for mood and memory performance. Results: ADP400-treated mice exhibited impaired memory performance and increased anxiety-like behaviors. Molecular analyses revealed heightened hyperphosphorylation of tau and increased β-amyloid levels, alongside decreased expression of AdipoRs and PP2A in the hippocampus, suggesting a critical role of AdipoRs in AD-like neuropathology. Furthermore, ADP400 treatment significantly reduced hippocampal adult neurogenesis, as indicated by decreased BrdU, Ki67, and DCX staining. Inhibiting peripheral adiponectin receptors could lead to tau hyperphosphorylation and accumulated β-amyloid levels. Conclusions: These findings highlight the critical role of peripheral manipulation of adiponectin receptors in modulating cognitive function and adult neurogenesis, offering insights into potential therapeutic strategies for AD and related cognitive disorders.